Field notes contributed by Dennis Henrickson, spring 1996 - Henrickson, Denniset al (1996)
Spring report of birds found in northwest Iowa contributed by Dennis Henrickson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1996. Epson - sheet feed/flatbed